The effect of the atmospheric mass on the way to the sunlight receiving surface on the spectral characteristics of solar radiation in the atmospheric layer under consideration AM 1.5 as a filter having appropriate transmittance for the corresponding wavel - Gorobetz, V. (Energy and Automation, 2016)
The method of calculation of heat pipe channels in the conditions of forced convection that takes into account the influence of nonisothermal surface on heat transfer coefficient. The numerical calculation and distributions of local heat transfer coefficient in the tube channel are received. A comparison with the results of calculation using of simplified modalities is conducted and the errors that occur is found.